A Phenomenological Study of Motivational–Emotional Tension and Communicative Engagement in Competitive Gamified EFL Learning - Rizkiy Mufida; Nirwanto Maruf (PT. Global Research Collaboration, 2026)
This study explores learners’ lived experiences of motivational-emotional tension in competitive gamified EFL learning and examines how this tension shapes their communicative engagement. A phenomenologically informed qualitative inquiry was conducted with 15 seventh-grade students from a junior high school in Gresik, East Java, Indonesia. Data were collected through semi-structured interviews, classroom observations, and student reflective notes and were analyzed using phenomenologically oriented thematic analysis supported by bracketing, repeated reading, coding, theme development, and cross-source triangulation. The analysis showed that learners experienced emotional fluctuation, social comparison, and differentiated responses to competitive pressure. These experiences shaped communicative engagement in three ways: motivational activation encouraged students to speak and participate, emotional pressure reduced verbal engagement through hesitation or silence, and learners' participation became selective depending on their confidence, anxiety, and perceived classroom position. The study contributes to EFL gamification research by showing that communicative engagement in competitive gamified learning is not a stable outcome of motivation alone, but a context-dependent process shaped by the interaction of motivational stimulation and emotional vulnerability. This study, therefore, recommends that gamified EFL instruction integrate emotional regulation, supportive feedback, and balanced competition alongside motivational incentives.